MITIGASI MASYARAKAT TENTANG BENCANA BANJIR DI NAGARI AUR BEGALUNG TALAOK KAECAMATAN BAYANG KABUPATEN PESISIR SELATAN (JURNAL SPASIAL, 2019)
This study aims at the Community Knowledge of Bajir disaster mitigation and community preparedness to Reduce the Risk of Flood Disaster at Nagari Aur Begalung Talaok, Bayang Subdistrict, southern coastal district. Descriptive research method The location of the study was at Nagari Aur Begalung Talaok, Bayang Subdistrict, southern coastal district. Population in the study The sample head of the family used an area probability sample and sample respondents based on the "proportional random sampling" method with a proportion of 20% of the total number of heads of family in Jorong, so that 23 respondents were obtained. Data analysis technique Using percentage formula and scale scales. The results of the study, First the public's knowledge of flood disasters. It can be concluded that the community's knowledge of flood disasters in the Bayang Nagari Aur Begalung Talaok District is quite understandable with a percentage of 43.51%, which means that based on the results of the community research, the understanding and knowledge of floods and damage are caused by flooding. Community preparedness about flood mitigation, It can be concluded that community preparedness to reduce the risk of floods in the Bayang Subdistrict Nagari Aur Begalung Talaok includes a notable percentage of 63.15%, which means that from the results of research the community does not understand preparedness to reduce risks, losses and damage caused with the flood disaster. Keyword: Flood Disaster. mitigation